Global Heat Uptake by Inland Waters. Issue 12 (15th June 2020) - Vanderkelen, I.; van Lipzig, N. P. M.; Lawrence, D. M.; Droppers, B.; Golub, M.; Gosling, S. N.; Janssen, A. B. G.; Marcé, R.; Schmied, H. Müller; Perroud, M.; Pierson, D.; Pokhrel, Y.; et al.
Abstract: Heat uptake is a key variable for understanding the Earth system response to greenhouse gas forcing. Despite the importance of this heat budget, heat uptake by inland waters has so far not been quantified. Here we use a unique combination of global‐scale lake models, global hydrological models and Earth system models to quantify global heat uptake by natural lakes, reservoirs, and rivers. The total net heat uptake by inland waters amounts to 2.6 ± 3.2 ×10 20  J over the period 1900–2020, corresponding to 3.6% of the energy stored on land. The overall uptake is dominated by natural lakes (111.7%), followed by reservoir warming (2.3%). Rivers contribute negatively (‐14%) due to a decreasing water volume. The thermal energy of water stored in artificial reservoirs exceeds inland water heat uptake by a factor ∼10.4. This first quantification underlines that the heat uptake by inland waters is relatively small, but non‐negligible. Plain Language Summary: Human‐induced emissions of CO2 and other greenhouse gases cause energy accumulation in the Earth system. Oceans trap most of this excess energy, thereby largely buffering the warming of the atmosphere. However, the fraction of excess energy stored in lakes, reservoirs, and rivers is currently unknown, despite the high heat capacity of water. Here we quantify this human‐induced heat storage, and show that it amounts up to 3.6% of the energy stored on land, while covering 2.58% of the land surface. The increase in heat storage from 1900 to 2020 is dominated by warming of lakes. The thermal heat contained in the water stored in man‐made reservoirs is about ten times larger. Our study overall highlights the importance of inland waters–next to oceans, ice and land–for buffering atmospheric warming, especially on regional scale. Key Points: We use a unique combination of lake models, hydrological models, and Earth System models to quantify global heat uptake by inland waters Heat uptake by inland waters over the industrial period amounts up to 2.6 × 10 20  J, or 3.6% of the continental heat uptake The thermal energy of the water trapped on land due to dam construction (26.8 × 10 20 J) is  10.4 times larger than inland water heat uptake